Legal Arrangements Regarding Soe Management In Increasing Public Welfare - Marimbo, Rizal Calvary; Silalahi, Jur Udin (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Public welfare is the goals of the Indonesian state which has been mandated in the 1945 constitution. SOE has a role in realizing this goal. However, in practice, SOEs face various challenges, one of which is related to governance within the SOEs themselves.Purposes of the Research: The purpose of this study is to analyze governance related to the laws and regulations governing SOE.Methods of the Research: The method in this research is normative juridical. The study used is a literature study. In answering the formulation of the problem in this study used a juridical and theoretical basis. The juridical basis used is the 1945 Constitution, Law Number 19 of 2003. The theoretical foundation used is the theory of legal ideals by Gustav.Results of the Research: Based on the research results, it was found that the role of SOEs in Indonesia is very important. There are many legal arrangements regarding BUMN. This certainly hinders the achievement of legal ideals, namely justice, certainty and the benefits of law. Therefore, it is necessary to create a legal entity in the form of an omnibus law in regulating SOEs.>